Power sharing strategy using H∞ controller between two distributed generation sources in islanded mode - Erum, Erum (2020)
This project addresses the problem of the primary controller of parallel-connected inverters in AC microgrid, which is operated in islanded mode. Voltage and frequency power sharing controller techniques are commonly used for sharing loads. However, this non-communication power sharing control technique has a disadvantage, where the frequency and voltage deviations are severe during a sudden load change. Currently, it can be fixed by using the communication-based secondary level. Therefore, the concept of non-communication network is needed for the DGs with fast restoration of voltage and frequency in order to maintain the stability and sensitivity of the islanded system. This project aims to develop a robust distributed H ∞ power sharing strategy to overcome the problem of restoration. The new controller would be able to enhance the performance and give a more reliable performance for power sharing, voltage and frequency restoration. Moreover, this project mainly focuses on the mathematical modelling of parallel-connected inverters, where the eigenvalues technique of the electric network is used to predict the stability of the islanded condition by applying eigenvalue technique. The proposed H ∞ power sharing control has established a condition for power sharing among the DGs and restores the voltage and frequency. This controller has shown the robustness effect in order to restore voltage and frequency and to satisfy the system performance. Finally, this H ∞ controller with robust and dynamic response is tested in islanded mode configuration, which has two DGs with identical power ratings connected to several local loads at the point of common coupling. The proposed robust controller’s theoretical concept is validated by using MATLAB Simulink, and it is compared with the conventional and existing secondary power sharing strategies that are also applied at the same electrical system. As result, the proposed controller can achieve better steady state performance and fast restored frequency within 0.002 s with rise time 0.05s while compared to 0.13 s rise time for existing secondary controller. Maximum overshoot is also reduced during the suddenvi load changed and good tracking performance efficiency by 95% as compared to the 90% efficiency of existing secondary controller and 85% conventional controller. Thus, it is able to restore voltage and frequency to nominal values and enhances power sharing according to inverter rating.